A new and highly efficient conservation treatment for deacidification and strengthening of aging paper by in-situ quaternization. (1st April 2019) - He, Bei; Lin, Qixuan; Chang, Minmin; Liu, Chuanfu; Fan, Huiming; Ren, Junli
Graphical abstract: Highlights: A new conservation treatment was developed by In-situ quaternization of aging paper. The deacidifatin and strengthening of aging paper were achieved together. The pH value was in the 7.5–9.0 range and the alkali storage amount was 220 mmol/Kg. The tensile strength and folding endurance were increased by 28.05% and 80%. Treated aging paper also had the great anti-bacteria and anti-aging performance. Abstract: Ancient papers, facing the threat of acidification, aging and microbial corrosion, need to be repaired due to their significance of history, art and culture research. In this work, a new and highly efficient approach was proposed to deacidify and strengthen aging paper by in-situ quaternization for the conservation, in which MgO nanoparticles dispersed in hexamethyldisiloxane was coated on the paper surface and the aqueous alkaline solution and the 2, 3-epoxypropyl trimethyl ammonium chloride/isopropyl alcohol/water mixture were sprayed in a closed reactor. Results showed that properties of ageing papers were improved after MSCE-8/2 treatment. The pH value was in the range of 7.5–9.0 and the maximum amount of alkali storage was 220 mmol/Kg. The tensile strength and folding endurance were increased by 28.05% and 80%, respectively. The fluctuation range of brightness and chromatic aberration was 0.14 and 1.27. Moreover, treated paper also had the great anti-bacteria and anti-aging effects.